Eco-design and sustainable development in the context of environmental security cities in connection with the development territories, as well post-war reconstruction - Gryshchenko, Roman; Ulytskyi, Oleg; Kryvosheiev, Maksym (My University, 2023)
In most Ukrainian cities, a negative ecological situation has developed due to the action of urbanization factors, including man-made loads, emissions of harmful substances, air, water, and soil pollution, and accumulation of industrial and household waste. Ecocide on a global scale has been taking place since the beginning of russia's full-scale treacherous invasion of Ukraine. Mass destruction of flora and fauna, poisoning water resources, and other actions that caused an ecological disaster were recorded in the temporarily occupied territories, as well as those already liberated. Therefore, the strengthening of environmental security, along with economic growth and social consensus, is the most important task in ensuring sustainable development and one of several priorities for state regional policy in Ukraine for the next 35 years.
Keywords: екодизайн; сталий розвиток; зелене будівництво; урбанізація; ecodesign; sustainable development; green building; urbanization; кафедра теплоенергетики та холодильної техніки